Atrial fibrillation and autonomic nervous system: A translational approach to guide therapeutic goals. Issue 2 (9th February 2021) - Rebecchi, Marco; Panattoni, Germana; Edoardo, Bressi; de Ruvo, Ermenegildo; Sciarra, Luigi; Politano, Alessandro; Sgueglia, Marianna; Ricagni, Chiara; Verbena, Sara; Crescenzi, Cinzia; Sangiorgi, Catia; Borrelli, Alessio; et al.
Abstract: The autonomic nervous system (ANS) is known to play an important role in the genesis and maintenance of atrial fibrillation (AF). Biomolecular and genetic mechanisms, anatomical knowledges with recent diagnostic techniques acquisitions, both invasive and non‐invasive, have enabled greater therapeutic goals in patients affected by AF related to ANS imbalance. Catheter ablation of ganglionated plexi (GP) in the left and right atrium has been proposed in varied clinical conditions. Moreover interesting results arise from renal sympathetic denervation and vagal nerve stimulation. Despite all this, in the scenario of ANS modulation translational strategies we necessary must consider the treatment or correction of dynamic factors such as obesity, obstructive sleep apnea, lifestyle, food, and stress. Finally, new antiarrhythmic drugs, gene therapy and "ablatogenomic" could be represent exciting future therapeutic perspectives. Abstract : Cardioneuroablation and cardioneuromodulation for patients affected by AF related to ANS imbalance.